Equilibrium, kinetics and thermodynamics of acid dye adsorption on palm oil empty fruit bunch - Tahir, Norini (2011)
A low-cost, easily obtained and eco-friendly adsorbents has been investigated as an ideal alternative to the current expensive methods such as using activated carbon for removing dyes from wastewater. This study investigated the use of palm oil empty fruit bunch (POEFB) fibre, an agricultural waste, for the removal of Acid Orange 51 (AO51) dye from aqueous solutions. Batch mode experiments were conducted at room temperature (28 ± 2)°C to study the effect of particle size (75 µm, 250 µm and 2 mm), initial dye concentrations (10-200 mg/L) and temperature (30-50 °C) of adsorption characteristics of AO51 dye onto treated and non-treated POEFB fibre. It was found that the adsorption removal of AO51 dye by treated POEFB fibre was ~5%, which was far lower than that of ~60% on the untreated POEFB fibre. The equilibrium adsorption isotherms and kinetics were further investigated for untreated POEFB fibre. The adsorption equilibrium data were analyzed by Langmuir, Freundlich and Temkin isotherm models. The results indicated that the equilibrium sorption fitted well with the Freundlich isotherm, displaying higher regression coefficient, R2 value. Adsorption kinetic data were modeled using the pseudo-first-order, pseudo-second-order and intraparticle diffusion models. It was shown that pseudo-second-order kinetic model could best describe the adsorption kinetics. Isotherms have also been used to obtain the thermodynamic parameters, namely enthalpy and entropy of adsorption. The result showed negative value for both enthalpy (-13.91 kJ/mol) and entropy (-38.43 J/mol K) changes. Based on the isotherm studies, it can be concluded that the adsorption of AO51 dye onto untreated POEFB is favorable via physical adsorption. Thermodynamically, the final adsorbed state of the dye molecule is lower in energy compared to initial state. These results indicate the potential of using POEFB fibre as a low-cost adsorbent material for adsorption of the AO51 dye from aqueous solutions.